2021 IEEE Sensors 2021
DOI: 10.1109/sensors47087.2021.9639741
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of Multi-Wavelength Optical Probe to Analyze Magnesium Implant Degradation Effects

Abstract: Near-infrared spectroscopy (NIRS) is a rapidly developing and promising technology with potential for spectrographic analysis. Understanding NIRS measurements on the implant-tissue interface for hydrogen gas formation as part of degradation is essential for interpreting the biodegradable Magnesium (Mg) based implants. This paper introduces novel NIR optical probe that can assess the state of Mg implant's degradation when in contact with biological tissues. A tissuemimicking phantom (TMP) to mimic biological ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…On average, the penetration depth of photons in the tissue is around 1/2 to 1/3 of the source-detector distance [ 41 ]. NIR light is estimated to reach a 3–3.5 mm depth, and the diffuse light is detected by the optical fiber inside the probe [ 29 , 42 ]. The same optical probe was recently used to validate the spectral absorption curves obtained from USPA [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On average, the penetration depth of photons in the tissue is around 1/2 to 1/3 of the source-detector distance [ 41 ]. NIR light is estimated to reach a 3–3.5 mm depth, and the diffuse light is detected by the optical fiber inside the probe [ 29 , 42 ]. The same optical probe was recently used to validate the spectral absorption curves obtained from USPA [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same optical probe was recently used to validate the spectral absorption curves obtained from USPA [ 43 ]. As shown in Figure 5 , we have used the molar extinction coefficient values to estimate the change in Hb and HbO 2 using an optical probe developed at Oslo Metropolitan University, Oslo, Norway [ 29 ]. In order to investigate different wavelengths, we must have DPF values for each wavelength.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PCA score plot for wavelength ranges from 1000 to 2000 nm is given in Figure 2 B, where more variation is observed in the Mg alloy as compared to the pure Mg and Ti. In a previous study, a tissue-mimicking gel prepared in the biochemistry lab at Oslo Metropolitan University, Norway, was used to investigate the effects of bubble formation in tissues, where we showed that the reflection of NIR light in the Mg alloy sample was 60% higher than the control one [ 46 ]. After each time point, disks were placed in the tissue-mimicking phantom to observe the reflection behaviour of bubbles in gels.…”
Section: Discussionmentioning
confidence: 99%